Plasma Neutrophil Gelatinase-Associated Lipocalin Reflects Both Inflammation and Kidney Function in Patients with Myocardial Infarction - Lindberg, Søren (Cardiorenal Med, 2016)
BACKGROUND/AIMS: Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as a marker for acute kidney injury and cardiovascular outcome. However, the relative importance of inflammation versus kidney function on plasma NGAL levels is uncertain, making the interpretation of plasma NGAL unclear. Accordingly, we investigated the relationship between plasma NGAL, inflammation and kidney function in patients with myocardial infarction (MI). METHODS: We prospectively included 584 patients with acute ST-segment elevation MI (STEMI) treated with primary percutaneous coronary intervention (PCI) from 2006 to 2008. Blood samples were drawn immediately before PCI. Additionally, we included 42 patients who had 4 blood samples drawn before and after PCI. Plasma NGAL was measured using a time-resolved immunofluorometric assay. Cross-sectional analyses were performed in these two single-center, prospective study cohorts. RESULTS: Estimated glomerular filtration rate (eGFR) was associated significantly more strongly with plasma NGAL when eGFR was abnormal compared to normal eGFR: a decrease in eGFR of 10 ml/min was associated with an increase in NGAL of 27% (18-36%) versus 4% (1-7%), respectively (p < 0.001). Leukocyte count and C-reactive protein were the main determinants of plasma NGAL in patients with normal eGFR, whereas eGFR was the main determinant at reduced kidney function. CONCLUSIONS: eGFR determines the association of NGAL with either inflammation or kidney function; in patients with normal eGFR, plasma NGAL reflects inflammation but when eGFR is reduced, plasma NGAL reflects kidney function, highlighting the dual perception of plasma NGAL. From a clinical perspective, eGFR may be used to guide the interpretation of elevated NGAL levels in patients with STEMI.